2016
DOI: 10.4236/am.2016.712115
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of Tuberculosis with Drug Resistance Effects

Abstract: Despite the enormous progress in prevention and treatment, tuberculosis disease remains a leading cause of death worldwide and one of the major sources of concern is the drug resistant strain, MDR-TB (multidrug resistant tuberculosis) and XDR-TB (extensively drug resistant tuberculosis). In this work, we extend the standard SEIRS epidemiology model of tuberculosis to include MDR-TB. For that, we considered compartments of susceptible, exposed, infected, resistant to a first line of treatment and recovered huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
0
12
0
4
Order By: Relevance
“…Household Size: Okoffo et al (2016) argue that a farmer with a larger household size will be more reluctant to spend his/her income on other things rather than using it in his household. However, Wairimu et al (2016) in relating to Abdulai et al (2008) revealed that households with large size have the numbers in terms of labor and therefore need more food hence will be willing to invest in agriculture. Concerning the inconsistency, this study hypothesizes household size to have both positive and negative influences on the growth of agriculture.…”
Section: Theoretical and Apriori Assumptionsmentioning
confidence: 99%
“…Household Size: Okoffo et al (2016) argue that a farmer with a larger household size will be more reluctant to spend his/her income on other things rather than using it in his household. However, Wairimu et al (2016) in relating to Abdulai et al (2008) revealed that households with large size have the numbers in terms of labor and therefore need more food hence will be willing to invest in agriculture. Concerning the inconsistency, this study hypothesizes household size to have both positive and negative influences on the growth of agriculture.…”
Section: Theoretical and Apriori Assumptionsmentioning
confidence: 99%
“…The iterative scheme RK-4 is utilized to solve the system, while the simulation is conducted through the MATLAB software. The parameter values for simulations are either from Ronoh et al [34] or reasonably chosen estimates. To do this, consider the parametric values as follows: at the initial level not treated or recovered population is considered.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Those who recover from MDR tuberculosis will move to the recovered cla. Given that there is no permanent immunity to tuberculosis, the recovered can lose their immunity and become susceptible again [4].…”
Section: Model Descriptionmentioning
confidence: 99%